On ancient medicine - Hippocrates. (Studies in Ancient Medicine, 2005)
The Hippocratic treatise On Ancient Medicine , a key text in the history of early Greek thought, mounts a highly coherent attack on the attempt to base medical practice on principles drawn from natural philosophy. This volume presents an up-to-date Greek text of On Ancient Medicine , a new English translation, and a detailed commentary that focuses on questions of medical and scientific method; the introduction sets out a new approach to the problem of the work's relationship to its intellectual context and addresses the contentious issues of its date, authorship, and reception. The book will be of interest to scholars of ancient medicine and ancient philosophy, as well as anyone concerned with the history of science and scientific method in antiquity.